Teacher talks and their importance for EFL learners - Sistyawan, Yan Nisa Intan; Purnamasari, Intan Izza; Azizah, Wafiq; Mardiningrum, Arifah (Universitas Muhammadiyah Sidoarjo, 2022)
In the learning process, the teacher talk is critical because it can help the success of the learning process, especially in mastering English as a foreign language (EFL) at various levels of education. This narrative review aims to determine the form of teacher talk and its importance to EFL learners at different educational levels. This study uses secondary data from 13 journal articles, which are research results on English teacher talk from various levels of education and settings and published between 2010-2020. The articles were accessed through several databases available to the researchers. All data were synthesized based on two research questions. The results of this study were the discovery of 4 categories of teacher talk forms based on (1) speech modification to facilitate learners, (2) the teacher's role as a facilitator, (3) responses to learners, and (4) their attitude in the classroom. Teacher talk is important because it can provide correct language input to learners. This narrative review can provide new insights to EFL teachers at all levels of education regarding the forms of teacher talk that they can use and how the talks can help the learning process and outcomes. HIGHLIGHTS: Teacher talk can be disseminated in the forms of speech modification to facilitate learners, teachers’ role as a facilitator, responses to learners, and teachers’ attitude in the classroom. Teacher talk is important because it can provide correct language input to learners and help them develop and improve their ability to speak English. The forms and benefits of the teacher talk cover any level of education contexts.